Regional brain changes occurring during disobedience to "experts" in financial decision-making. - Victoria Y M Suen (PLoS ONE, 2014)
It is well recognized that individuals follow "Expert" advice, even when flawed and offers no advantage, and sometimes leads to disadvantages. The neurobiology underlying this is uncertain, and in particular there is an incomplete understanding of which brain regions are most involved when individuals chose to disobey an expert. To study this we examined functional magnetic resonance imaging (fMRI) differences during an investment game where subjects received differentially credible investment advice. Participants (n = 42; 32 males) played an investment game, in which they could Buy or Not Buy a sequence of stocks. The better they did, the more money they made. Participants received either "Expert" advice or "Peer" advice. Those receiving Expert advice were told the advice came from a certified financial "Expert". Those receiving Peer Advice were told the advice was that of the student administering the scans, who deliberately dressed and acted casually. Both streams of advice were predetermined and identical. The advice was scripted to be helpful initially, but progressively worse as the task continued, becoming 100% wrong by the end of the task. Subjects receiving Expert Advice followed the advice significantly longer on average, even though this was progressively worse advice. Thus, following Expert advice had poorer consequences for individuals, but this did not dissuade them from continuing to follow the advice. In contrast, when subjects disobeyed Expert advice they exhibited significant anterior cingulate cortex (ACC) and superior frontal gyrus activation relative to those disobeying Peer advice. These findings may suggest that in subjects who defy authority, or believe they are doing so (in this case by disobeying an "Expert") there is increased activation of these two brain regions. This may have relevance to several areas of behavior, and the potential role of these two brain regions in regard to disobedience behavior requires further study.